Controllable Synthesis of Monodisperse Er(3+)-Doped Lanthanide Oxyfluorides Nanocrystals with Intense Mid-Infrared Emission - He, Huilin (Sci Rep, 2016)
Monodisperse lanthanide oxyfluorides LnOF (Ln = Gd, Y) with mid-infrared emissions were controllably synthesized via a mild co-precipitation route and a subsequent heat-treatment. The detailed composition and morphology were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM) and high resolution transmission electron microscopy (HRTEM). The results showed that monodisperse GdOF:Er(3+) were nano-riced shape with length about 350 nm and width about 120 nm, while the quasi-spherical YOF:Er(3+) were uniform nanocrystals with an average size around 100 nm. The influence of calcination temperature on the size and phase transition of LnOF nanocrystals was also investigated. The photoluminescence (PL) spectra indicated that the 2.7 μm emission of Er(3+) had achieved in both GdOF and YOF nanocrystals, which were calcined at different temperatures. In addition, the decay time of both (4)I(13/2) and (4)I(13/2) energy levels corresponding to Er(3+) in YOF nanocrystals were also studied in detail. The results suggested that both rice-shaped GdOF nanocrystals and YOF nanocrystals could provide suitable candidate materials for nanocrystals-glass composites, which could be a step forward to the realization of mid-infrared laser materials.